3D printing of a recycled copolyester of terephthalic acid, cyclohexanedimethanol and tetramethylcyclobutanediol. (15th January 2023) - Bhagia, Samarthya; Kore, Surbhi; Wasti, Sanjita; Ďurkovič, Jaroslav; Kováč, Ján; Zhao, Xianhui; Andrews, Hunter B.; Martin, Madhavi; Gallego, Nidia C.; Vaidya, Uday; Ozcan, Soydan
Abstract: 2, 2, 4, 4-Tetramethyl-1, 3-cyclobutanediol (TMCD) is a diol monomer for terephthalic acid (TPA) class of copolyesters that can increase the glass transition temperature and mechanical strength in comparison to conventional TPA polyesters. TMCD-modified poly (1, 4-cyclohexylenedimethylene terephthalate) (PCTT) has been used to manufacture consumer products with good toughness, heat resistance and clarity. However, the suitability of PCTT in 3D printing had not been evaluated. Therefore, consumer plasticware was used as the starting material to investigate the suitability of this copolyester for fused deposition modeling (FDM). Chemical structure, mechanical properties, thermal behavior and viscoelastic properties of this copolyester were studied. NMR spectroscopy found that the copolyester had cyclohexanedimethanol (CHDM) and TMCD contents at 76.5 mol% and 20 mol% of total diol, respectively. 280 °C printing temperature and 110 °C bed temperature were suitable conditions for printing. Tg of PCTT was 103 °C (25 °C higher than PETG). Young's modulus and impact strength of printed PCTT were at least 100% and 65% higher than printed PETG, respectively. The ease of printing, superior mechanical properties and Tg (103 °C) make the PCTT random copolyester highly applicable in additive manufacturing. Graphical abstract: Image 1 Highlights: 3D printing of TMCD-modified PCT copolyester (PCTT) was performed. Extrusion/printing temperature of 280 °C and bed temperature of 110 °C were suitable. Young's modulus of printed PCTT was at least 100% higher than printed PETG. Impact strength of printed PCTT was at least 65% higher than printed PETG. Glass transition temperature of PCTT (103 °C) was higher than PETG (78 °C).